FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI E-GOVERNMENT (STUDI PADA PEMERINTAH DAERAH TINGKAT PROVINSI DI INDONESIA) - Annasia Sophia Dewi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2013)
This research aims to analyze the factors that affect the successes implementation of public financial disclosure through e-government. Factors tested in this research are debt (DSCR), the number of councillors, GDP per capita, citizen education level, population, and region own source revenue. Sample in this research were selected using purposive sampling method, that is e-government on 33 provinces in Indonesia. The samples are divided into two categories, provinces reporting the transparency of financial management through e-government and provinces not reporting. Statistical methods used in this study is the logistic regression at a significance level 5%. Result of this research indicate that the factor debt (DSCR), the number of councillors, and region own source revenue significantly influence the implementation of e-government. While other factors, GDP per capita, citizen education level, and population not indicate any significant effect on the implementation of e-government.